2017
DOI: 10.1159/000479867
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Subcutaneous Recombinant Parathyroid Hormone (1–34) Infusion in the Management of Childhood Hypoparathyroidism Associated with Malabsorption

Abstract: Background/Aims: Hypoparathyroidism associated with malabsorption can be particularly challenging to manage due to limited and erratic intestinal absorption of calcium and vitamin D analogues, resulting in episodes of hypo- or hypercalcaemia. We evaluated the role of continuous subcutaneous recombinant parathyroid hormone (rhPTH 1–34) infusion (CSPI) in children with hypoparathyroidism associated with intestinal malabsorption resistant to conventional therapy. Method: Four patients (8–13 years of age), with sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…Clinical trials in adults have shown good efficacy, however long term safety needs to be further studied 30. Continuous subcutaneous infusion of recombinant PTH1–34 has successfully been used in children with hypoparathyroidism who were difficult to manage on conventional therapy31 32; however, its use is not licensed in children and no randomised trials have been performed .…”
Section: Treatment Of Hypocalcaemiamentioning
confidence: 99%
“…Clinical trials in adults have shown good efficacy, however long term safety needs to be further studied 30. Continuous subcutaneous infusion of recombinant PTH1–34 has successfully been used in children with hypoparathyroidism who were difficult to manage on conventional therapy31 32; however, its use is not licensed in children and no randomised trials have been performed .…”
Section: Treatment Of Hypocalcaemiamentioning
confidence: 99%
“…Rest of the studies were excluded because of the following reasons: study done in children;[ 10 ] prospective design or unrelated population[ 11 12 13 25 26 27 28 29 30 31 32 33 34 35 36 ]; duplication of data[ 37 38 ]; comparison of different PTH doses[ 39 40 41 ]; evaluation of cost-effectiveness of PTH therapy[ 42 ]; and use of either pump therapy or continuous subcutaneous PTH infusion. [ 5 43 44 45 46 ]…”
Section: R Esultsmentioning
confidence: 99%
“…[ 4 ] Moreover, when hypoparathyroidism is associated with malabsorptive disorders (autoimmune polyendocrine syndrome type 1), oral supplementations with calcium and vitamin D are less effective. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…Winer et al previously demonstrated that synthetic human parathyroid hormone (PTH 1‐34) given by subcutaneous injection or pump effectively maintained serum calcium in the normal range with reduced levels of urine calcium excretion compared to conventional therapy 7‐9 . For many patients with severe hypoparathyroidism, replacement PTH therapy reduced the need for acute emergency IV calcium infusions and improved quality of life 10‐12 . Recombinant human PTH 1‐34 (rhPTH; FORTEO ® ) was approved as a treatment for osteoporosis in 2002 and is used worldwide as an off‐label hormonal replacement therapy in patients with hypoparathyroidism who are refractory to conventional therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant human PTH 1‐34 (rhPTH; FORTEO ® ) was approved as a treatment for osteoporosis in 2002 and is used worldwide as an off‐label hormonal replacement therapy in patients with hypoparathyroidism who are refractory to conventional therapy. Studies have demonstrated that rhPTH 1‐34 reduced urine calcium excretion and adverse events, and provides stable calcium levels in the normal range 10‐14 . Studies with recombinant human PTH 1‐84 demonstrated its efficacy when added to conventional therapy 15,16 .…”
Section: Introductionmentioning
confidence: 99%